Currency options in exchange risk management and toxic derivatives in the financial market - Brodowska-Szewczuk, Jolanta (Management and Administration Journal, 2023)
The aim of this article is the presentation of currency options as derivatives which are used in currency risk management. There is an analysis of the possibility of building proper option strategies by enterprises so that they could limit the exchange rate risk. The invalid construction of toxic options is also presented in the article. The afore-mentioned toxic derivatives did not secure companies against risk but were the cause of huge financial losses in many Polish enterprises.